Spectroscopy of z=0 Lifshitz Black Hole - Gulnihal Tokgoz; Izzet Sakalli (Advances in High Energy Physics)
We studied the thermodynamics and spectroscopy of a 4-dimensional, z=0 Lifshitz black hole (Z0LBH). Using Wald’s entropy formula and the Hawking temperature, we derived the quasi-local mass of the Z0LBH. Based on the exact solution to the near-horizon Schrödinger-like equation (SLE) of the massive scalar waves, we computed the quasi-normal modes of the Z0LBH via employing the adiabatic invariant quantity for the Z0LBH. This study shows that the entropy and area spectra of the Z0LBH are equally spaced.